15. RESEARCH ON CLINICAL, PARA-CLINICAL CHARACTERISTICS AND RISK FACTORS OF BIRTH ASPHYXIA (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical, paraclinical characteristics and to identify risk factors of birth asphyxia.Subject and methods: The case-control study included 61 asphyxiated newborns in the case group and 122 non-asphyxiated newborns in the control group, treated at the Department of Intensive Care - Neonatal Intensive Care, Pediatric Center, and Obstetrics Department of Hue Central Hospital. The study was conducted from February 2022 to July 2023.Results: The most common clinical symptoms are hypothermia (21.3%), coma (6.6%), lethargy/lack of flexibility (42.6%), and tachycardia (16.4%). The rates of increased SGOT, increased SGPT and increased blood creatinine were 27.9%, 11.5% and 4.9%, respectively. Multivariate analysis showed that maternal general anesthesia [OR = 16,1 (95% CI: 1,7-149,8)], placental abruption and/or placenta previa [OR = 14,8 (95% CI: 1,5-151,9)], prolonged rupture of membranes [OR = 14,0 (95% CI: 3,4-57,2)], fetal distress [OR = 3,3 (95% CI: 1,3-8,5)] and intrauterine growth retardation [OR = 2,7 (95% CI: 1,1-6,3)] are independent factors increasing the risk of neonatal asphyxia (p < 0.05).Conclusion: Mothers should be screened for risk factors for birth asphyxia to reduce the rate of newborn asphyxia.
Keywords: Risk factor, birth asphyxia.